ANALISIS KEBIJAKAN CYBER CRIME DALAM HUKUM POSITIF DI INDONESIA - Intan Permata Sari; Irma Wati Pasaribu, Muhammad Zahien Akbar AS, Berlian Cikka Octanelsha (INTELIGENSIA MEDIA, 2024)
Technological developments move in line with the legal dynamics that occur in Indonesia. Information and communication technology has a huge impact on the regulatory revolution as well as social, cultural and community life. Apart from the positive impacts that can result from technological developments, there are also negative impacts, namely social media crimes or known as cyber crimes. Legitimate control over cyber crime is a challenge for cybercrime which is developing with the information technology revolution. Policy regarding cyber crime in positive law in Indonesia is the aim of writing this research. The research method used in this research is a normative legal approach. Data processing is carried out through library research, such as literature and scientific works related to research problems. The results of this research show that there are more than 7 regulations in the form of special laws and regulations in the Criminal Code (KUHP) which regulate cyber crime, then other policies are in Law no. 11 of 2008 as amended in Law Number 19 of 2016 concerning Information and Electronic Transactions